Mbah Ndoro Payung: History, Epigraphy, and Religious Tourism of the Tomb - Ahmad Baihaqi; Fikrul ‘Ilmi Nafi’uddin; Iin Nur Zulaili; Nguliyatun Nuriya (Universitas Islam Negeri Sumatera Utara, 2026)
This study examines the historical and spiritual values contained in the tomb of Mbah Ndoro Payung (Syekh Bentong) in Gresik as part of the local Islamic cultural heritage. The research focuses on three main aspects: the history of Mbah Ndoro Payung, an epigraphic study of Islam on his tomb, and an analysis of the tomb's role as a religious tourist destination. This study uses qualitative methods with historical and epigraphic approaches. The historical approach is used to trace the life and contributions of Mbah Ndoro Payung in the process of Islamization in Java. Meanwhile, the epigraphic approach is used to analyze the inscriptions on the tombstone to reveal the identity, religious messages, and cultural symbols contained therein. The research findings indicate that Mbah Ndoro Payung was a Chinese-Muslim Islamic missionary who played a role in the spread of Islam through cultural, social, and humanitarian approaches. Epigraphic analysis revealed inscriptions of Surah Ash-Shaff, verse 13, and the shahada on Mbah Ndoro Payung’s tombstone, as well as Surah Al-Baqarah, verse 257, on his wife’s tombstone. These inscriptions demonstrate strong Islamic values while also illustrating the process of acculturation between Islamic traditions and Majapahit culture, as reflected in the ornamentation and style of the tombstones. In addition to its historical and religious significance, Mbah Ndoro Payung’s tomb continues to serve as a vibrant socio-religious space through the tradition of the “haul,” pilgrimage activities, and the community’s religious practices. The site also holds potential for the development of religious tourism, which can support the preservation of local Islamic cultural heritage and provide economic benefits to the surrounding community.